Nietzsche e a questão do corpo na modernidade - LEAL, Julie Christie Damasceno (Universidade Federal do Pará, 2017)
The present dissertation aims to develop an interpretation concerning the conception of body in Nietzsche, taking into account the perspectival bias and instinctive dimension of whole body, as well as the multiplicity of forces inherent in the investigation of the body. In view of that, according to the assimilation of Nietzsche, the notion of body places itself as conducting wire of his lucubrations, especially because the resumption of such a question demonstrates pertinent for thinking about the body in the course of Western thought, since the concept of ancient Greeks, passing the aesthetic Socratism, Platonism and Christian morality to modernity and its reverberations in relation to nihilism process. That said, it is particularly important to provide a critique of the poor understanding of body erected by traditional philosophy, while emphasizing the appropriation of Platonism by Christian morality, which resulted in the depreciation of the body and degeneration of the instincts and most vital bodily impulses, become sick, a fact that contributed of illness tendencies and belittlement of man in modernity. For that, we intend to analyze the notion of body crossed by the established valuations, both from aesthetic, and moral, cultural and philosophical, especially in the texts The Birth of Tragedy, Human Too Human, Beyond Good and Evil, Genealogy of Morals and Thus spoke Zarathustra, basic to place the question of the body in the dimensions that made possible their rise and decay. In this manner, the dissertation this shows that relevant because it allows the deepening on a question that arises latently in the context of Western thought: body notion, taken from the bias proposed by the German philosopher, as a forces field and conflict in modernity.